COMPARISON OF POSTOPERATIVE PAIN IN TRANSFACIAL MESH COMPARED WITH TACKER FIXATION IN INTRAPERITONEAL ONLAY MESH REPAIR OF ABDOMINAL WALL HERNIA AT A TERTIARY CARE HOSPITAL - TAHIR, JA; AKHTAR, N; HIRAAJ, MURK; CHOUDRY, SU; SHAHZAD, A (Biological and Clinical Sciences Research Journal, 2024)
Postoperative pain is a critical factor influencing recovery and patient satisfaction in abdominal wall hernia repair. Intraperitoneal onlay mesh (IPOM) repair is a widely used technique, and the method of mesh fixation—transfacial sutures or tackers—can significantly impact postoperative outcomes. Objective: To compare postoperative pain and other clinical outcomes between transfacial mesh fixation and tacker fixation in patients undergoing IPOM repair for abdominal wall hernias. Methods: This randomized controlled trial included 60 patients undergoing elective IPOM repair at a tertiary care hospital in Pakistan. Participants were randomly allocated into two groups: transfacial fixation (Group A) and tacker fixation (Group B). Postoperative pain was assessed using the Visual Analog Scale (VAS) 24 hours post-surgery. Secondary outcomes included duration of surgery, hospital stay, and complications. Data were analyzed using IBM SPSS version 26, with a p-value ≤0.05 considered significant. Results: The mean VAS score was significantly lower in Group A (3.9 ± 0.7) compared to Group B (5.3 ± 0.8, p<0.001). Group A also had shorter hospital stays (3.1 ± 0.5 days vs. 3.7 ± 0.6 days, p=0.015), though operative time was longer (95 ± 10 minutes vs. 82 ± 9 minutes, p=0.032). Complication rates, including wound infection and mesh migration, were low and comparable between groups. Conclusion: Transfacial mesh fixation is associated with lower postoperative pain and shorter hospital stays compared to tacker fixation, making it a preferable method for IPOM repair in abdominal wall hernias. These findings support the use of transfacial fixation as an effective technique in hernia repair, with implications for improving patient care in resource-limited settings.